2021
DOI: 10.1002/csc2.20434
|View full text |Cite
|
Sign up to set email alerts
|

Cotton phenotyping and physiology monitoring with a proximal remote sensing system

Abstract: Substantial progress has been made in developing sensor-based proximal phenotyping systems for cotton (Gossypium hirsutum L.), but research is needed to improve in-season prediction of lint yield and to improve accuracy in monitoring crop water stress using such a system. Here, we report on results of a 2-yr field study in which a proximal remote sensing system (measuring canopy height, spectral indices [normalized difference vegetation index, NDVI], and canopy temperature) was deployed every 2 wk over plots o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Along with restructuring the crop architecture, good agricultural practices are crucial. Modernization of agricultural practices through advanced satellite imagery and remote sensing‐based information on environmental conditions such as soil moisture and nutrient properties, temperature variations during flowering and seed filling stages, and rainfall and storm updates can minimize yield loss in major crops globally (Adams et al ., 2021; De Swaef et al ., 2021; Pineda et al ., 2021). Artificial intelligence could be efficiently utilized to predict yield in crops and even minimize use of fertilizers according to soil nutrient profile.…”
Section: Developmental Regulators: Steps Towards the ‘Ideal’ Plant Ar...mentioning
confidence: 99%
“…Along with restructuring the crop architecture, good agricultural practices are crucial. Modernization of agricultural practices through advanced satellite imagery and remote sensing‐based information on environmental conditions such as soil moisture and nutrient properties, temperature variations during flowering and seed filling stages, and rainfall and storm updates can minimize yield loss in major crops globally (Adams et al ., 2021; De Swaef et al ., 2021; Pineda et al ., 2021). Artificial intelligence could be efficiently utilized to predict yield in crops and even minimize use of fertilizers according to soil nutrient profile.…”
Section: Developmental Regulators: Steps Towards the ‘Ideal’ Plant Ar...mentioning
confidence: 99%
“…In this study, models based on raw bands of near-infrared and red reflectance were also able to moderately estimate IPAR f throughout the growing season, further highlighting the importance of these two reflectance bands in explaining the variability in IPAR f . NDVI, which is also a function of near-infrared and red reflectance bands, has been used to predict cotton LAI and canopy cover (Ritchie et al, 2010;Adams et al, 2021). Guillen-Climent et al ( 2012) also reported that out of several VIs, NDVI was best correlated with IPAR f for crops with homogenous canopies such as wheat, maize, and soybean.…”
Section: Figurementioning
confidence: 99%
“…This involves identifying and enhancing traits related to nutrient use efficiency, water stress tolerance, disease resistance, and response to environmental cues. By incorporating these traits into improved seeds, breeders can provide farmers with crops that perform optimally in precision agriculture systems (Basu;Parida, 2023;Abichou;Solan;Andrieu, 2019;Adams;Ritchie;Rajan, 2021).…”
Section: Plant Breeding In the Era Of Precision Agriculturementioning
confidence: 99%